Prepartum and postpartum concentrations of lipids and lipoproteins in dairy cows - Mutlu Sevinç; Abdullah Başoğlu; Fatih Birdane; İsmail Öztok; Mustafa Yenice (Eurasian Journal of Veterinary Sciences)
In this study, cholesterol, triglyceride; HDL, LDL and VLDL concentrations in sera were analysed from the seventh month of pregnancy to the second month of lactation in 13 Holstein dairy cows. Triglyceride and VLDL concentrations were significantly elevated (p<0.001) and HDL concentration was significantly decreased (P<0.001) in the first month of lactation. LDL concentration was significantly decreased (p<0.001) in the eighth month of pregnancy and at parturation, and it was significantly elevated (p<0.001) in the first two months of lactation. Cholesterol level significantly increased (p<0.001) in the second month of lactation, and VLDL level in the seventh month of pregnancy was significantly decreased (p<0.001).